2020
DOI: 10.1371/journal.pone.0238309
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Korean version of the Reading the Mind in the Eyes Test

Abstract: The Reading the Mind in the Eyes Test (RMET) is one of the most widely used instruments for assessing the ability to recognize emotion. To examine the psychometric properties of the Korean version of the RMET and to explore the possible implications of poor performance on this task, 200 adults aged 19–32 years completed the RMET and the Korean version of the 20-item Toronto Alexithymia Scale (TAS-20K), the cognitive empathy domain of the Korean version of the Interpersonal Reactivity Index (IRI-C), and the Bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…In the emotional valence 3-factor, overall model fit was slightly improved, but some fit indices were still poor. By looking at the results of previous studies, similar to the results of the present study in the single-factor and 3-factor model, the overall fit indices did not meet the above mentioned established criteria [ 22 , 44 ], and even a study in the Korean subjects that reported relatively fair model fit, was not seemed to be good in CFI [ 49 ]. For ease of understanding, emotions are generally categorized such as positive, negative, and neutral, but in reality, emotions are made up of more complex and subtle combinations of reactions.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the emotional valence 3-factor, overall model fit was slightly improved, but some fit indices were still poor. By looking at the results of previous studies, similar to the results of the present study in the single-factor and 3-factor model, the overall fit indices did not meet the above mentioned established criteria [ 22 , 44 ], and even a study in the Korean subjects that reported relatively fair model fit, was not seemed to be good in CFI [ 49 ]. For ease of understanding, emotions are generally categorized such as positive, negative, and neutral, but in reality, emotions are made up of more complex and subtle combinations of reactions.…”
Section: Discussionsupporting
confidence: 56%
“…By looking at the results of previous studies, similar to the results of the present study in the single-factor and 3-factor model, the overall fit indices did not meet the above mentioned established criteria, 22,44 and even a study in the Korean subjects that reported relatively fair model fit, was not seemed to be good in CFI. 49 For ease of understanding, emotions are generally categorized such as positive, negative, and neutral, but in reality, emotions are made up of more complex and subtle combinations of reactions. In line with Vellante et al, 24 proposed that the RMET may also have factor structures of more diverse dimensions rather than a few categories.…”
Section: Discussionmentioning
confidence: 99%
“…Reading the Mind in the Eyes Test (RMET) [ 35 , 36 ] assessed participants’ emotion perception abilities. This 4-option multiple-choice test consists of 36 photographs of the eye region embedding different emotional valences (8 positive, 12 negative, and 16 neutral expressions).…”
Section: Methodsmentioning
confidence: 99%
“…The BSI includes three factors: (1) desire for death, (2) preparation for death, and (3) active suicidal desire. A high total score indicates higher levels of suicidal thoughts, and Cronbach's alpha of the Korean version of the BSI was 0.74 (52).…”
Section: Beck Scale For Suicide Ideation (Bsi)mentioning
confidence: 99%